2017
DOI: 10.14260/jemds/2017/1157
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mast Cells in Leprosy- A Study of 62 Cases

Abstract: BACKGROUNDMast cells have received little attention in leprosy, but evidence linking them with delayed-type hypersensitivity reactions raises the possibility that they may be of some importance in leprosy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The data about MCs in leprosy, a chronic dermato-neurological granulomatous disease caused by Mycobacterium leprae , are controversial. Most of the studies indicate an increased number of MCs in skin biopsies of lepromatous lesions, in comparison with other leprosy forms ( 309 311 ), except for one study in which a higher dermal MC number was found around granulomas in skin biopsies from patients with tuberculoid or mild-borderline leprosy in comparison to lepromatous leprosy biopsies ( 312 ). A more recent study showed that there is a greater amount of degranulated versus intact MCs and a predominance of tryptase positive versus chymase positive MCs in the skin of leprosy patients, independently of leprosy form and reactional episodes ( 313 ).…”
Section: Detrimental Roles Of Mast Cells During Antimicrobial Responsementioning
confidence: 99%
“…The data about MCs in leprosy, a chronic dermato-neurological granulomatous disease caused by Mycobacterium leprae , are controversial. Most of the studies indicate an increased number of MCs in skin biopsies of lepromatous lesions, in comparison with other leprosy forms ( 309 311 ), except for one study in which a higher dermal MC number was found around granulomas in skin biopsies from patients with tuberculoid or mild-borderline leprosy in comparison to lepromatous leprosy biopsies ( 312 ). A more recent study showed that there is a greater amount of degranulated versus intact MCs and a predominance of tryptase positive versus chymase positive MCs in the skin of leprosy patients, independently of leprosy form and reactional episodes ( 313 ).…”
Section: Detrimental Roles Of Mast Cells During Antimicrobial Responsementioning
confidence: 99%